Association between nickel and multiple metabolic outcomes: The mediating roles of lipid metabolism and inflammation - Zuqiang Fu; Shijie Zhou; Zhenkun Weng; Geyu Liang; Aihua Gu (Ecotoxicology and Environmental Safety)
The relationship between nickel exposure and metabolic disease remains unclear, the study aims to investigate the association between nickel exposure and various metabolic disease outcomes and elucidate potential underlying mechanisms. Using data from the 2017–2018 National Health and Nutrition Examination Survey (NHANES), we evaluated nickel exposure in relation to eight metabolic outcomes: coronary heart disease (CHD), heart failure (HF), heart arrest (HA), angina, stroke, diabetes, hypertension, and chronic kidney disease (CKD). The findings demonstrated that each natural logarithm increase in urinary nickel concentration was significantly associated with higher risk of HF (OR=1.663, 95 % CI: 1.000–2.765), diabetes (OR=1.713, 95 % CI: 1.341–2.187), and CKD (OR=1.347, 95 % CI: 1.078–1.683). Furthermore, individuals with higher nickel exposure demonstrated an elevated risk of CHD (OR=2.439, 95 % CI: 1.008–5.903, P-trend=0.046) and diabetes (OR=2.494, 95 % CI: 1.526–4.075, P-trend<0.001) in a dose-dependent manner. Restricted cubic spline analyses showed no evidence of nonlinear associations between nickel exposure and other outcomes (all P > 0.05). Mediation analyses identified lipid metabolism disruption as a significant mediator for nickel's effects on CHD (Low density lipoprotein cholesterol [LDL-C], 9.76 %, P = 0.040; Total cholesterol [TC], 18.75 %, P < 2 ×10−16) and HF (LDL-C, 16.60 %, P = 0.040). Inflammatory activation mediated the relationship between nickel and CKD (Lymphocyte/White blood cell [Lym/WBC], 10.56 %, P < 2 ×10−16; Monocyte/Lymphocyte [Mono/Lym], 10.19 %, P < 2 ×10−16). Notably, nickel-induced inflammatory responses also appeared to dysregulate lipid metabolism, potentially contributing to diabetes risk (LDL-C, 26.35 %, P < 2 ×10−16; TC, 15.27 %, P < 2 ×10−16; Neutrophils/Lymphocyte [Neu/Lym], 2.42 %, P = 0.040). These results suggest that nickel exposure is associated with increased risks of CHD, HF, CKD, and diabetes, potentially through mechanisms involving lipid metabolism disturbances and inflammatory activation.